Iran's position on the armed Palestinian factions until 1979 - Rady, Qusai Mahmoud (Al-Adab Journal, 2022)
There is no doubt that Iran during the reign of Shah Muhammad Reza Pahlavi dealt with the Palestinian issue in contrast to its dealings with the armed factions affiliated with the leadership of the Palestine Liberation Organization, as the Shah’s regime was sympathetic to the legitimate demands of the Palestinian people, if it was for an Islamic or humanitarian motive. It was completely rumored. The Shah tried to leave a positive impression on the Arab and Islamic countries, that Iran stands united with the Palestinian cause, but at the same time the Shah was also keen on Iran's interests, and he always asserts that Iran, despite its sympathy with the Palestinian cause, is It was often invoked by reason and logic, which emphasizes the necessity of dealing with Israel as a fait accompli, especially as it is supported by major countries such as the United States of America and Britain, as it is unreasonable for the Shah to antagonize Israel merely because of the desire of Arab and Islamic countries to do so, and he always repeated the slogan Politics is one thing, trade and economy are another thing, not to mention that the policy of the United States of America in the Middle East has made it imperative for its allies, Iran and Israel, to work together as required by the stage. based on protecting their interests in the Middle East. It seems that this was one of the most important reasons for the dispute between the Palestinian armed factions and the regime of the Shah, and it seems clear that the emergence of the armed factions affiliated with the leadership of the Palestine Liberation Organization in the mid-sixties of the twentieth century has caused a chronic headache for the regime of the Shah, especially when it was realized that These factions sought rapprochement with the Iranian revolutionary forces opposed to his regime, by providing them with financial and military support. The Shah believed that some of these armed Palestinian factions had deliberately done so, not out of their desire to support the revolutionary movements in the Middle East, but rather these factions work for the benefit of a number of The Arab countries whose relations with Iran are experiencing some tension and tension, especially Egypt during the era of President Gamal Abdel Nasser, Iraq and the Gulf states, so the Shah was cautious in dealing with these armed Palestinian factions, as he was aware that some of the leaders of these factions do not follow the orders of an organized leadership. Palestinian liberation, but it works for the intelligence of a number of Arab countries. As a result, the relationship between the Shah’s regime and the armed Palestinian factions witnessed various aspects. The Shah repeatedly tried to woo the Palestine Liberation Organization, pledging material and moral support to it, in return for stopping their support for the Iranian opposition, as well as stopping their dealings with some leaders of the armed Palestinian factions affiliated with the leadership The Liberation Organization, which the Shah accused of being behind all the damage to Iran's interests internally and externally, which he called extremist wings of terrorism. Apparently, the leadership of the Liberation Organization represented by its Chairman Yasser Arafat was ambivalent about the regime in Iran. Sometimes he praised the Shah's performance towards Arab issues, especially the Palestinian cause, and at other times he admitted that the Palestine Liberation Organization had played a major role in supporting the Iranian opposition and destabilizing the regime. The Shah’s rule and then his overthrow in 1979, and this was confirmed by his first visit to Iran after the fall of the Pahlavi regime and his meeting with Ayatollah Imam Ruhollah Mousavi Khomeini. Then a new era of distinguished relations began between the Palestine Liberation Organization, with all its armed factions, and the Islamic Republic of Iran.